Histidine-rich glycoprotein in metabolic dysfunction-associated steatohepatitis-related disease progression and liver carcinogenesis - Foglia, Beatrice; Sutti, Salvatore; Cannito, Stefania; Rosso, Chiara; Maggiora, Marina; Casalino, Alice; Bocca, Claudia; Novo, Erica; Protopapa, Francesca; Ramavath, Naresh Naik; Provera, Alessia; Gambella, Alessandro; et al. (Frontiers in Immunology, 2024)
Background Metabolic dysfunction-associated steatotic liver disease (MASLD), previously non-alcoholic fatty liver disease (NAFLD), is a leading cause of chronic liver disease worldwide. In 20%–30% of MASLD patients, the disease progresses to metabolic dysfunction-associated steatohepatitis (MASH, previously NASH) which can lead to fibrosis/cirrhosis, liver failure as well as hepatocellular carcinoma (HCC). Here we investigated the role of histidine-rich glycoprotein (HRG), a plasma protein produced by hepatocytes, in MASLD/MASH progression and HCC development. Methods The role of HRG was investigated by morphological, cellular, and molecular biology approaches in (a) HRG knock-out mice (HRG−/− mice) fed on a CDAA dietary protocol or a MASH related diethyl-nitrosamine/CDAA protocol of hepatocarcinogenesis, (b) THP1 monocytic cells treated with purified HRG, and (c) well-characterized cohorts of MASLD patients with or without HCC. Results In non-neoplastic settings, murine and clinical data indicate that HRG increases significantly in parallel with disease progression. In particular, in MASLD/MASH patients, higher levels of HRG plasma levels were detected in subjects with extensive fibrosis/cirrhosis. When submitted to the pro-carcinogenic protocol, HRG−/− mice showed a significant decrease in the volume and number of HCC nodules in relation to decreased infiltration of macrophages producing pro-inflammatory mediators, including IL-1β, IL-6, IL-12, IL-10, and VEGF as well as impaired angiogenesis. The histopathological analysis (H-score) of MASH-related HCC indicate that the higher HRG positivity in peritumoral tissue significantly correlates with a lower overall patient survival and an increased recurrence. Moreover, a significant increase in HRG plasma levels was detected in cirrhotic (F4) patients and in patients carrying HCC vs. F0/F1 patients. Conclusion Murine and clinical data indicate that HRG plays a significant role in MASLD/MASH progression to HCC by supporting a specific population of tumor-associated macrophages with pro-inflammatory response and pro-angiogenetic capabilities which critically support cancer cell survival. Furthermore, our data suggest HRG as a possible prognostic predictor in HCC patients with MASLD/MASH-related HCCs.